Consequences of late-stage non-small cell lung cancer cachexia on muscle metabolic processes - Murton, Andrew J.; Maddocks, Matthew; Stephens, Francis B.; Marimuthu, Kanagaraj; England, Ruth; Wilcock, Andrew (Elsevier, 2016)
Introduction: Loss of muscle is common in patients with advanced non-small cell lung cancer (NSCLC), and contributes to the high morbidity and mortality of this group. The exact mechanisms behind the loss of muscle are unclear. Patients and methods: To investigate this, 4 patients with stage IV NSCLC meeting the clinical definitions for sarcopenia and cachexia were recruited, along with 4 age-matched healthy volunteers. Following an overnight fast, biopsies were obtained from the vastus lateralis and key components associated with inflammation and the control of muscle protein, carbohydrate and fat metabolism assessed. Results: Compared to healthy volunteers, significant increases in mRNA levels for interleukin-6 and NFκB signalling were observed in NSCLC patients along with lower intramyocellular lipid content in slow-twitch fibres. While a significant decrease in phosphorylation of mTOR signalling protein 4E-BP1 (Ser65) was observed along with a trend towards reduced p70 S6K (Thr389) phosphorylation (P=0.06), there was no difference between groups for mRNA levels of MAFbx and MuRF1, chymotrypsin-like activity of the proteasome, or protein levels of multiple proteasome subunits. Moreover, despite decreases in intramyocellular lipid content, no robust changes in mRNA levels for key proteins involved in insulin signalling, glycolysis, oxidative metabolism or fat metabolism were observed.